What is the contribution of two genetic variants regulating VEGF levels to type 2 diabetes risk and to microvascular complications? - Amélie Bonnefond; Pierre-Jean Saulnier; Maria G Stathopoulou; Niels Grarup; Ndeye Coumba Ndiaye; Ronan Roussel; Mohsen Azimi Nezhad; Aurélie Dechaume; Olivier Lantieri; Serge Hercberg; Torsten Lauritzen; Beverley Balkau; et al. (PLoS ONE)
Vascular endothelial growth factor (VEGF) is a key chemokine involved in tissue growth and organ repair processes, particularly angiogenesis. Elevated circulating VEGF levels are believed to play a role in type 2 diabetes (T2D) microvascular complications, especially diabetic retinopathy. Recently, a genome-wide association study identified two common single nucleotide polymorphisms (SNPs; rs6921438 and rs10738760) explaining nearly half of the variance in circulating VEGF levels. Considering the putative contribution of VEGF to T2D and its complications, we aimed to assess the effect of these VEGF-related SNPs on the risk of T2D, nephropathy and retinopathy, as well as on variation in related traits.SNPs were genotyped in several case-control studies: French and Danish T2D studies (N(cases) = 6,920-N(controls) = 3,875 and N(cases) = 3,561-N(controls) = 2,623; respectively), two French studies one for diabetic nephropathy (N(cases) = 1,242-N(controls) = 860) and the other for diabetic retinopathy (N(cases) = 1,336-N(controls) = 1,231). The effects of each SNP on quantitative traits were analyzed in a French general population-based cohort (N = 4,760) and two French T2D studies (N = 3,480). SNP associations were assessed using logistic or linear regressions.In the French population, we found an association between the G-allele of rs6921438, shown to increase circulating VEGF levels, and increased T2D risk (OR = 1.15; P = 3.7×10(-5)). Furthermore, the same allele was associated with higher glycated hemoglobin levels (β = 0.02%; P = 9.2×10(-3)). However, these findings were not confirmed in the Danes. Conversely, the SNP rs10738760 was not associated with T2D in the French or Danish populations. Despite having adequate statistical power, we did not find any significant effects of rs6921438 or rs10738760 on diabetic microvascular complications or the variation in related traits in T2D patients.In spite of their impact on the variance in circulating VEGF, we did not find any association between SNPs rs6921438 and rs10738760, and the risk of T2D, diabetic nephropathy or retinopathy. The link between VEGF and T2D and its complications might be indirect and more complex than expected.